Prevalence, trends, and maternal risk factors of adverse birth outcomes from a hospital-based birth defects surveillance system in Kampala, Uganda, 2015–2022 - Ronald Kusolo; Daniel Mumpe-Mwanja; Robert Serunjogi; Augustina Delaney; Joyce Namale-Matovu; Kenneth Mwambi; Phoebe Monalisa Namukanja-Mayambala; Jennifer L. Williams; Cara T. Mai; Yan Ping Qi; Philippa Musoke (BMC Pregnancy and Childbirth)
Abstract Background Adverse birth outcomes (ABOs) cause significant infant morbidity and mortality in resource-limited settings. Many of the maternal risk factors associated with ABOs can be prevented. We present the prevalence, trends, and risk factors of selected ABOs from a hospital-based birth defects surveillance program in Kampala, Uganda. Methods We analyzed data for all mothers with singleton deliveries collected from four urban hospitals between 2015 and 2022. Prevalence of preterm birth [PTB], low birth weight [LBW], small for gestational age [SGA], and stillbirth [SB] and maternal HIV seroprevalence were calculated among 222,427 births. SB was defined as infant born without life ≥ 28 weeks of gestation, LBW as term live birth weighing < 2500 g and PTB as live birth born < 37 weeks of gestation. Time trends of ABOs by maternal HIV status and age were computed using quasi-Poisson regression model and presented graphically. Risk factor associations were estimated using robust Poisson models adjusting for infant sex, hospital of delivery, and birth year. Results Prevalence of PTB, LBW, SGA, and SB were 14.8%, 4.3%, 17.8%, and 3.1%, respectively. Maternal HIV seroprevalence was 7.7%. Compared to mothers aged 25–34 years, young adolescents 10–18 years was associated with PTB (adjusted risk ratio [aRR]: 1.44, 95% confidence interval (CI): 1.38–1.50); LBW (1.65,1.51–1.81); and SGA (1.18; 1.12–1.24). HIV seropositivity was associated with PTB (1.18; 1.14–1.22), LBW (1.54; 1.43–1.65), and SGA (1.28; 1.23–1.33). Compared to starting ANC in the first trimester, no antenatal care (ANC) was associated with PTB (2.44; 2.33–2.56), LBW (1.80; 1.55–2.09), SGA (1.37; 1.27–1.49), and SB (3.73; 3.32–4.15) and late attendance with LBW (1.09; 1.02–1.16), SGA (1.26; 1.22–1.30), and SB (1.09; 1.02–1.17). Our findings also indicate a rising trend in PTB among adolescent and young women aged 10–24 years, and a declining trend in LBW and SGA over time (ptrend < 0.05 for all). Conclusions Young maternal age, maternal HIV, and late or no ANC attendance were associated with ABO. Childbearing in the ages 25–34, preventing HIV in women, and supporting early and frequent ANC attendance are important in improving birth outcomes.